9‐Borabicyclononane Bipyridyl Complexes: Synthesis, Luminescence, and Electronic Characterization. Issue 39 (23rd July 2020) - Chrzanowski, Matthew; Collins, Stephanie; Zeller, Matthias; Gray, Thomas G.
Abstract : This work presents the use of organoboron compounds as anolytes in redox flow batteries. Through the study of their structural, electrochemical, and photophysical properties, four bipyridyl boronium salts show potential for application in such batteries. The compounds were synthesized in moderate to high yields by previously published methods. We find when using chelating bipyridyl‐based substituents, the complexes undergo two reversible reductions; however, when switching to phenanthroline‐based substituents, the reduction events are no longer reversible. Density‐functional theory calculations indicate that the chelating nitrogen heterocycle is the locus of reduction and fluorescence. Abstract : Organoboron analogues of viologens were synthesized and characterized structurally, photophysically, and electrochemically. Bipyridine‐based N ^ N chelates demonstrate two reversible reduction events, demonstrating their applicability for use in redox‐flow batteries.